Where in a time constrained throwing task is the speed-accuracy trade-off? - Liang, Y.; Kamiel-Skeete, A.; Pettitt, A.; Hiley, M. J. (Journal of Sports Sciences, 2023)
Previous research on fielding in cricket and baseball has focused on the technique and speed-accuracy trade-off of the throw in isolation from a typical sequence of fielding actions; approach, gather and throw. The present study aimed to determine whether a speed-accuracy trade-off existed in fielding and where within the above sequence the trade-off occurs. Participants, who were elite cricketers, were required to run to a stationary ball and throw to the centre of a target in order to run-out a virtual batter. High-speed video was used to record the time of approach, time in contact with, and time of flight of the ball. Two-way ANOVAs were used to determine differences in group (gender) and condition (instructions to prioritise speed or accuracy). A speed-accuracy trade-off was found, with both groups being quicker in the approach and spending less time in contact with the ball in the speed condition; however, the horizontal velocity of the throw remained the same in both conditions. It was proposed the drop in accuracy in the speed condition may be associated with less time spent aiming. It was found that instructions triggered a change in throwing technique for 31% of the participants, which requires further investigation.